Hubungan Antara Durasi dan Frekuensi Paparan Layar Media Elektronik (screen time) dengan Perkembangan Bahasa pada Balita di Puskesmas Kendal Kerep di Kota Malang - Annisa Hasanah; Nadia Paramita Bhakti Putri; Iwan Sis Indrawanto; Rahayu (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The incidence of speech and language delay disorders in children in Indonesia ranges from 2.3-24.6%. The American Academy of Pediatrics (AAP) recommends that electronic media screen exposure should not be given to children under 18 months of age. While at the age of 2 to 4 years, exposure to electronic media screens is suggested to be limited to about 1 hour per day. The influence of the duration of the digital devices in electronic media screen exposure (screen time) greatly impacts language development. This study aims to determine the correlation between duration and frequency of exposure to screen time on language development of toddlers at Kendalkerep health center in Malang city. This study used a cross-sectional method with questionnaires and KPSP measuring instruments to determine language development in toddlers at Kendalkerep Health Center in Malang City. There was a correlation between duration and frequency of exposure to screen time on language development of toddlers at Puskesmas Kendalkerep in Malang City with a spearman correlation of duration and language development of r=0.375 (Moderate), while the spearman correlation of frequency and language development was r=0.424 (Moderate). The study concluded that there was a correlation between duration and frequency of exposure to Electronic Screen Time on language development of toddlers at Puskesmas Kendalkerep in Malang City.